Transwomen in South Indian Tamil Films: A View on Representation - Raguram, S.; Vijayatharsiny, V. (Proceedings of the 4th Jaffna University International Research Conference (JUICe2018), 2018)
The gender differences between men and women are being prioritized in society in general. Challenging the traditional gender binary the subject of the third gender becomes a topic of discussion these days. In the past, the existence of the third gender created some social conflicts. The social perception towards the third gender is changing considerably. Their existence is getting social acceptance these days. Many countries in the world recognize transgenders are rightful citizens, while movies do not do the same – they created different opinions and thoughts about them. The cinema is considered the most influential media in the formation of popular opinions. Hence, there is a necessity to understand the representation of the third gender, particularly the transgender, through the lenses of media ethics. This study attempt to explore the system of representation of transgender in Tamil movies, particularly in the movies produced in Tamil Nadu. The objective of this research is to study how the characters of transgender are portrayed and to understand the roles of these characters, body language and symbols. The representation of transgender in South Indian Tamil movies was measured using elements like the number of scenes allocated for transgender, the role of the character, design of dresses used, body language expressions and symbols. 18 South Indian Tamil movies released in the period between 2006 and 2016 consisting of roles allocated to transgender were used as the sample for the study. Data and information gathered from the contents of movies and interviews with relevant persons were analyzed in quantitative and qualitative manners. Based on the representation given to transgender, the study concluded that the South Indian Tamil movies give a negative perception about transgender and the importance given to them through constrictive characters remains very low comparatively. The study discovered that there were negative and positive portrayal aspects of transgender in South Indian Tamil movies. The portrayal expressed through dialogues, expression of behaviour, background music and technologies related to cinematography were seems to be positive with respect to transgender in South Indian Tamil movies. At the same time; the role of the characters, designing of dresses, expression of body language and symbols of transgender characters are negatively portrayed.
Keywords: South Indian Tamil Films; Transgender; Transwomen; Positive Representation; Negative Representation